Transmission mechanisms of toi-cultural at the current stage of society development (Journal of Philosophy Culture and Political Science, 2025)
In this study, «toi» in traditional Kazakh culture is considered one of the directions for preserving and spreading national values and customs, as well as maintaining and spreading national values, customs, and social norms in modern social development. Being at the junction of intangible cultural heritage and developing modern experience, «toi» serves not only as a holiday, but also as a means of spiritual and educational development, making a significant contribution to the formation of the Kazakh identity.Despitethechangesin its developmentand the traditionalKazakhculture, «toi»remains a vital transmission channel fromgenerationtogeneration. Within this framework, asaba is the primary cultural mediator responsible for forming and preserving wedding traditions.The study highlights the role of asaba as a cultural agent (regulatory intermediary) who contributes to adapting and preserving the «toi» culture in modern conditions.The purpose of the scientific article is to determine the role of «toi» as a phenomenon of Kazakh culture in spiritual and educational upbringing and the formation of Kazakh identity.The authors used qualitative research to achieve their research goals and the «snowball» method to select respondents.The study was conducted in Shymkent, and the respondents were event management agency specialists, organisers, and toastmasters.The study reveals that «toi» culture and the associated etiquette are declining, while various forms of entertainment are increasing. This suggests that «toi» culture and its etiquette tend to decline from day to day, and there is also an increase in various types of entertainment. In addition, the importance of «toi» as a means of transmitting traditional Kazakh culture from generation to generation and the need to develop standardised concepts such as «asaba ethics» and «toi code» are emphasised.The study results show a high demand for asaba's services: it was found that many families are willing to pay a significant amount for a professional driver, who can significantly influence the successful, interesting holding of the event.A small number of participants in this study revealed several limitations, as the empirical part of this scientific study was conducted in Shymkent. However, since «toi» is a dynamically developing cultural phenomenon and has a number of limitations, the empirical part of this scientific study was conducted in Shymkent.However, since «toi» is a dynamically developing cultural phenomenon with multiple limitations, and the empirical part of this scientific study was conducted in Shymkent, further research is planned to explore its role in the National Cultural Continuum.